New anticancer agents and therapeutic strategies in development for solid cancers: a clinical perspective. Issue 1 (1st February 2004) - Awada, Ahmad; Mano, Max; Hendlisz, Alain; Piccart, Martine
In addition to well-known chemotherapeutic agents used in the treatment of solid cancers, promising novel cytotoxic agents are being investigated. Among them are analogs of existing cytotoxic agents, aimed at improving the therapeutic index, and new families such as the epothilone compounds. Agents that target the tyrosine kinase-dependent pathways, farnesyl transferase modulators, Raf kinase inhibitors, antisense molecules to Bcl-2 and proteasome modulators, agents that bind to key proteins involved in critical phases of the cell cycle, as well as antiangiogenesis strategies, are all promising approaches in the treatment of solid cancers. The combination of cytotoxics, hormonal agents or radiotherapy with new molecular-targeted therapies represents one of the main strategies to improve survival in solid cancers. A clinical perspective of these agents as monotherapy or combination therapy will be presented in this paper.